Pertanggungjawaban Notaris Selaku Pejabat Pembuat Akta Tanah Atas Penyalahgunaan Kepercayaan Terkait Penggelapan Sertifikat - Aryani, Vioni Fadhila; Pulungan, M. Sofyan (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to describe and analyze the Notary Public’s accountability as an LDMO for the abuse of trust related to certificate embezzlement and legal remedies that can be taken by the appeared as the aggrieved party for this action. The type of research used in this research is normative juridical research. The type of data used in this research is secondary data through document studies or literature studies. The legal materials that have been collected are then processed and analyzed systematically using qualitative data analysis methods. The results showed that the Notary Public as LDMO has accountability for the abuse of authority given based on trust related to embezzlement of certificates in the management of land rights transfer registration. The accountabilities that can be charged are administrative, criminal, and moral accountabilities. In addition, legal remedies taken by parties who feel aggrieved are categorized through two channels, namely the non-litigation by reporting to the local Regional Supervisory Council of Notary Public and the litigation by reporting to the local police. Based on this conclusion, it is recommended that the Notary Public and the Notary Public as LDMO carry out their duties and positions by upholding and complying with the applicable code of ethics and laws and regulations. Then an amendment to Law No. 2 of 2014 and Government Regulation No. 24 of 2016. In this case, it is necessary to add provisions on criminal sanctions against the Notary Public’s actions that violate the Office Law and the code of ethics to have a deterrent effect. In addition, the Notary Public and LDMO will be more careful, responsible, and professional in carrying out their professions and offices.